PENGARUH KEMITRAAN DAN MANAJEMEN PENGETAHUAN TERHADAP KEUNGGULAN BERSAINGUNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Purba, Saut; Haloho, Elizabeth; Harefa, Hilda Syaf’aini (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the influence of partnerships and knowledge management, both partially and simultaneously, on the competitive advantage of Santo Thomas Catholic University, Medan. The population in this study was 6,540 active students for the 2022/2023 academic year. The sample in the study was 98 respondents using the Simple Random Sampling technique. The analytical methods used are instrument tests, classical assumption tests, hypothesis tests, coefficient of determination tests and multiple linear regression analysis. The research results show (1) Based on the Partial Test (t Test) partnership has a positive and significant effect on the competitive advantage of Santo Thomas Catholic University Medan, (2) Based on the Partial Test (t Test) knowledge management has a positive and significant effect on the competitive advantage of Santo Thomas Catholic University Medan, and (3) Based on the Simultaneous Test (F Test) of partnership and knowledge management simultaneously competitive advantage of Santo Thomas Catholic University Medan